Up-To-Date Challenges for the Conservation, Rehabilitation and Energy Retrofitting of Higher Education Cultural Heritage Buildings - Pereira, Luísa Dias (2021)
In higher-education world heritage sites, the conservation and energy retrofitting of heritage buildings (HBs) is an important vector for their development, competitiveness and welfare. To guarantee their ongoing use, these buildings must be adapted to face current and emerging societal challenges: (i) the conservation of cultural heritage and the maintenance of their original characteristics and identity; (ii) the transformation of heritage sites into tourist centers that energize the local economy, generating revenue and jobs; (iii) the adaptation of the buildings to new uses and functions that demand energy retrofitting strategies to satisfy today’s standards of thermal comfort, indoor environmental quality (IEQ) and energy efficiency; (iv) tackling impacts of climate change, particularly global warming and extreme weather events; and finally, (v) the implementation of strategies to mitigate the impact of a growing number of tourists. The combined implications of these challenges require a comprehensive approach with interrelated measures strongly reliant on the use of technology and innovation. This work aims to discuss how higher-education cultural HBs can be rethought to serve these expectations. Moreover, a multidisciplinary intervention framework is provided to discuss how HBs can respond to the challenges and risks of rehabilitation, energy retrofitting, climate change and increasing tourism.